2018
DOI: 10.1093/infdis/jiy262
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Gammaherpesvirus Shedding in Saliva Among Ugandan Children and Their Mothers

Abstract: In summary, in this population, individuals were more likely to shed EBV than KSHV in saliva. We identified several factors, including child's sex, that influence KSHV shedding, and we detected an inverse relationship between EBV and KSHV shedding, suggesting a direct or indirect interaction between the two viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
4
26
0
3
Order By: Relevance
“…The use of traditional alcoholic beverages we observed to be associated with anti‐KSHV Abs perhaps indicates a possible contribution of local plant extracts or products of fermentation (e.g., butyrate) to viral reactivation. Conversely, use of mosquito nets was associated with lower likelihood of KSHV detection in blood, plausibly because of reduced exposure to malaria, which we have reported as a risk factor for KSHV seroprevalence and DNA detection . In accordance with previous perplexing reports about KS risk and KSHV shedding, we also found that HIV‐uninfected smokers had a lower likelihood of KSHV detection in blood (although they had slightly higher anti‐K8.1 Ab levels).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The use of traditional alcoholic beverages we observed to be associated with anti‐KSHV Abs perhaps indicates a possible contribution of local plant extracts or products of fermentation (e.g., butyrate) to viral reactivation. Conversely, use of mosquito nets was associated with lower likelihood of KSHV detection in blood, plausibly because of reduced exposure to malaria, which we have reported as a risk factor for KSHV seroprevalence and DNA detection . In accordance with previous perplexing reports about KS risk and KSHV shedding, we also found that HIV‐uninfected smokers had a lower likelihood of KSHV detection in blood (although they had slightly higher anti‐K8.1 Ab levels).…”
Section: Discussionsupporting
confidence: 89%
“…Cross‐sectional studies such as this cannot investigate time as source of variation in shedding; rather, our aim is to compare the behaviour of the two viruses and investigate the cofactors that may affect shedding and salivary VL. We found that the prevalence of KSHV salivary shedding was moderate, while EBV was excreted almost universally; this is consistent with what we described in a mother–child cohort of HIV‐uninfected Ugandans . Participants with KS were more likely than controls to shed both viruses.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations